Il pensiero di due cristiani dell’Occidente sulle relazioni internazionali: Reinhold Niebuhr e Giorgio La Pira - Zonova, Tatiana (Rivista di studi politici internazionali, 2022)
The Author examines the legacy of two great Christian thinkers, the American Reinhold Niebuhr and the Italian Giorgio La Pira, both very influent during the Cold War. Niebuhr was a protestant theologian and political adviser to the American establishment. The Mayor of Florence, La Pira, was a prominent Italian statesman and an eminent catholic thinker. The Author analyzes theirs views on international relations, in particularly on the western policy towards the Soviet Union, the use of nuclear weapons, the war in Vietnam and the communist issue. The legacy of the two thinkers is highly topical in front of the ethical dimension of choices needed in international politics today.